2020
DOI: 10.1111/sji.13007
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated microRNA‐132 in T helper 17 cells activates hepatic stellate cells to promote hepatocellular carcinoma cell migration in vitro

Abstract: MicroRNAs play an important role in the modulation of the immune system. T helper 17 (Th17) cells are involved in the modulation of the tumour microenvironment. However, the function of miRNA in Th17 cells in the tumour microenvironment is unclear. In this study, we analysed miR‐132 expression in Th17 cells and assessed the function of miR‐132 on Th17 cell differentiation. In addition, the effect of miR‐132 on Th17 cells in the tumour microenvironment, especially hepatic stellate cells (HSCs), was confirmed. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Apart from immune diseases, the relation between miRNAs and Th17 has been demonstrated in other pathologies. In hepatocellular carcinoma–derived Th17 cells, a recent article showed increased miR-132 levels, another upregulated miRNA in our study, and demonstrated that the use of a miR-132 mimic accelerates Th17 differentiation in vitro ( Feng et al, 2021 ). At the kidney level, there are few studies on the role of miRNAs in Th17 differentiation ( Lavoz et al, 2020a ).…”
Section: Discussionsupporting
confidence: 66%
“…Apart from immune diseases, the relation between miRNAs and Th17 has been demonstrated in other pathologies. In hepatocellular carcinoma–derived Th17 cells, a recent article showed increased miR-132 levels, another upregulated miRNA in our study, and demonstrated that the use of a miR-132 mimic accelerates Th17 differentiation in vitro ( Feng et al, 2021 ). At the kidney level, there are few studies on the role of miRNAs in Th17 differentiation ( Lavoz et al, 2020a ).…”
Section: Discussionsupporting
confidence: 66%
“…Th17 cells were reported to inhibit growth and metastasis via the stimulation of cytotoxic T cells and natural killer cells within the TME [ 55 ]. In the HCC microenvironment, Th17 cells have a non-pathogenic phenotype and produce anti-inflammatory cytokines [ 56 , 57 , 58 ]. Classical M1 macrophages engage the inflammatory response and anti-tumor immunity, while alternative M2 macrophages are defined by their anti-inflammatory properties in the immunosuppressive microenvironment [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the HCC microenvironment, Th17 cells have a non-pathogenic phenotype and produce anti-inflammatory cytokines [ 56 , 57 , 58 ]. Classical M1 macrophages engage the inflammatory response and anti-tumor immunity, while alternative M2 macrophages are defined by their anti-inflammatory properties in the immunosuppressive microenvironment [ 58 ]. Previous studies have shown that, due to the role of tumor-associated macrophages in immune invasion, higher levels of tumor-activated macrophages are positively associated with poor prognosis in HCC patients [ 49 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also explored the function of miRNAs in Th17 cells in the TME of HCC. During Th17 cell differentiation, treatment with the miR-132 mimic promoted the differentiation of Th17 cells, leading to a higher percentage of Th17+ cells and higher secretion of IL-17 and IL-22 ( 97 ). Furthermore, miR-132-overexpressing Th17 cells could enhance the activation of hepatic stellate cells (HSCs), inducing HCC cell EMT and migration ( 97 ).…”
Section: Ncrnas Regulate Cellular Components Of the Tmementioning
confidence: 99%